2008
DOI: 10.1002/adma.200702753
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing Functionalized Carbon Nanohorns with Primary Phagocytic Cells

Abstract: Functionalized carbon nanohorns (f‐CNH) are uptaken by macrophages, without affecting cell viability. f‐CNH induce the production of reactive oxygen species and of pro‐inflammatory cytokines. The level of inflammation, although moderate, should be taken into consideration when using f‐CNH for drug delivery. However, it could be exploited as an intrinsic f‐CNH adjuvant function for biomedical applications requiring some activation of the immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…S3) (44,45). The low CNH toxicity was also confirmed in both in vitro (41,44,45) and in vivo studies (41)(42)(43). We found that BSA-CNH has lower cytotoxicity than BSA-CNTs (Fig.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…S3) (44,45). The low CNH toxicity was also confirmed in both in vitro (41,44,45) and in vivo studies (41)(42)(43). We found that BSA-CNH has lower cytotoxicity than BSA-CNTs (Fig.…”
Section: Resultssupporting
confidence: 75%
“…4E). Immunohistochemical staining revealed the absence of undesired inflammatory responses, although CNH uptake by macrophages (41,42) stained with rabbit anti-ionized calcium binding adaptor molecule 1 was observed (53) (Fig. 4F).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Until now, studies at the cellular level on SWCNHs were mainly focused on the interaction between SWCNHs and non-polarized cells particularly macrophages, and have mostly emphasized on the cellular uptake and intracellular trafficking, but seldom on transportation. [14][15][16][17][18][19][20][21] It is worth noting that, depending on the routes of administration, nanocarriers may have to cross different physiological barriers in their journey towards their target. 22,23 These barriers are mainly polarized epithelia, such as the gastrointestinal tract, the lungs, and the blood-brain barrier.…”
mentioning
confidence: 99%